Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine the [tex]\(x\)[/tex]-intercept and [tex]\(y\)[/tex]-intercept for the given equation [tex]\( -6x + 3y = 18.9 \)[/tex], you need to solve the equation for each intercept separately.
### Finding the [tex]\(x\)[/tex]-intercept:
1. The [tex]\(x\)[/tex]-intercept occurs where [tex]\(y = 0\)[/tex].
2. Substitute [tex]\(y = 0\)[/tex] into the equation:
[tex]\[ -6x + 3(0) = 18.9 \][/tex]
This simplifies to:
[tex]\[ -6x = 18.9 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{18.9}{-6} \][/tex]
4. Simplify the result:
[tex]\[ x = -3.15 \][/tex]
Thus, the [tex]\(x\)[/tex]-intercept is [tex]\(-3.15\)[/tex].
### Finding the [tex]\(y\)[/tex]-intercept:
1. The [tex]\(y\)[/tex]-intercept occurs where [tex]\(x = 0\)[/tex].
2. Substitute [tex]\(x = 0\)[/tex] into the equation:
[tex]\[ -6(0) + 3y = 18.9 \][/tex]
This simplifies to:
[tex]\[ 3y = 18.9 \][/tex]
3. Solve for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{18.9}{3} \][/tex]
4. Simplify the result:
[tex]\[ y = 6.3 \][/tex]
Thus, the [tex]\(y\)[/tex]-intercept is [tex]\(6.3\)[/tex].
### Final answers:
[tex]\[ x\text{-intercept} = -3.15 \][/tex]
[tex]\[ y\text{-intercept} = 6.3 \][/tex]
### Finding the [tex]\(x\)[/tex]-intercept:
1. The [tex]\(x\)[/tex]-intercept occurs where [tex]\(y = 0\)[/tex].
2. Substitute [tex]\(y = 0\)[/tex] into the equation:
[tex]\[ -6x + 3(0) = 18.9 \][/tex]
This simplifies to:
[tex]\[ -6x = 18.9 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{18.9}{-6} \][/tex]
4. Simplify the result:
[tex]\[ x = -3.15 \][/tex]
Thus, the [tex]\(x\)[/tex]-intercept is [tex]\(-3.15\)[/tex].
### Finding the [tex]\(y\)[/tex]-intercept:
1. The [tex]\(y\)[/tex]-intercept occurs where [tex]\(x = 0\)[/tex].
2. Substitute [tex]\(x = 0\)[/tex] into the equation:
[tex]\[ -6(0) + 3y = 18.9 \][/tex]
This simplifies to:
[tex]\[ 3y = 18.9 \][/tex]
3. Solve for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{18.9}{3} \][/tex]
4. Simplify the result:
[tex]\[ y = 6.3 \][/tex]
Thus, the [tex]\(y\)[/tex]-intercept is [tex]\(6.3\)[/tex].
### Final answers:
[tex]\[ x\text{-intercept} = -3.15 \][/tex]
[tex]\[ y\text{-intercept} = 6.3 \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.